Pulmonary artery pathologies in Alagille syndrome: a meta-analysis - Yuan, Shi-Min (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Alagille syndrome, caused by mutations in the gene encoding Jagged1 (JAG1), a ligand in the Notch signaling pathway, is an autosomal dominant disorder with developmental abnormalities affecting the liver, heart, eyes, face and skeleton. The aim of the present study is try to disclose the clinical features, management and outcomes of pulmonary artery stenosis associated with Alagille syndrome. By comprehensive literature retrieval, 38 articles involving 401 patients were recruited for this study. The pertinent variables closely related to pulmonary artery stenosis in patients with Alagille syndrome were comprehensively analyzed by following the PRISMA guidelines. The management of pulmonary artery pathologies, especially a severe type of pulmonary artery stenosis in Alagille syndrome, is a concerned matter. Publications of literature retrieval of recent 3 decades were the study material of this article. The pulmonary artery pathologies, especially the severe type of pulmonary artery stenosis in Alagille syndrome, warrant surgical or interventional treatments. After the procedures, the right ventricular to left ventricular pressure ratio was reduced by 25%. There were no intergroup differences in terms of recovery, reintervention and mortality rates between interventionally and surgically treated patients. Transcatheter treatment is preferable due to less trauma. Surgical treatment of pulmonary artery stenosis can be performed currently with intracardiac defect repair.